Optimization of photothermal therapy conditions through diffusion analysis based on the initial injection radius of AuNPs - Kim, Donghyuk; Kim, Hyunjung (International Journal for Numerical Methods in Biomedical Engineering, 2024)
Anticancer treatment is performed in various ways, and photothermal therapy (PTT) is gaining traction from a noninvasive treatment perspective. PTT is a treatment technique based on the photothermal effect that kills tumors by increasing their temperature. In this study, gold nanoparticles (AuNPs), which are photothermal agents, were used in numerical simulations to determine the PTT effect by considering diffusion induced changes in the distribution area of the AuNPs. The treatment effect was confirmed by varying the initial injection radius of AuNPs represented by the injection volume, the elapsed time after injection of AuNPs, and the laser intensity. The degree of maintenance of the apoptotic temperature band in the tumor was quantitatively analyzed by the apoptotic variable. Ultimately, if the initial injection radius of AuNPs is 0.7 mm or less, the optimal time to start treatment is 240 min after injection, and for 1.0 and 1.2 mm, it is optimal to start treatment when the elapsed time after injection is 90 and 30 min, respectively. This study identified the optimal treatment conditions for dosage of AuNPs and treatment start time in PTT using AuNPs, which will serve as a reference point for future PTT studies.
Keywords: Apoptotic; Condition; Diffusion analysis; Elapsed time after injection; Gold nanoparticle; Gold Nanoparticles; Injection radius; Optimisations; Photothermal therapy; Thermal damage; Animals; Diffusion; Gold; Humans; Metal Nanoparticles; Photothermal Therapy; apoptosis; elapsed time after injection; gold nanoparticles; injection radius; photothermal therapy; thermal damage